Genome editing technology and regenerative dentistry: a narrative review - Silva, Andria da (2023)
The revolutionary prospects of regenerative dentistry and CRISPR genome editing in reshaping oral healthcare practices is such an exciting potential to discover. With a focus on addressing the challenges posed by poor oral hygiene and conventional tooth replacement methods, the research delves into the potential of regenerative dentistry through tissue engineering. Applications of this novel technique are investigated using a few examples from the world of dentistry. In addition, the revolutionary potential of CRISPR gene editing technology in dentistry will be introduced. Through a comprehensive discussion, the implications, challenges, and ethical considerations surrounding the implementation of these cutting-edge technologies are explored. The results highlight the enormous promise of CRISPR technology and regenerative dentistry while highlighting the need for more study and pragmatic issues.